ANALISIS DETERMINAN POLA PENANGANAN PASCAPANEN PINANG (Areca catechu.L) DI KABUPATEN TANJUNG JABUNG BARAT - Aulia Hakim, Aras; Suandi; Rosyani (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
Jambi Province has the three largest and best-quality betel nut producing districts namely Tanjung Jabung Barat Regency, Tanjung Jabung Timur Regency, Muaro Jambi Regency, but Tanjung Jabung Barat Regency has the largest land area and production. With the limited technology and traditional post-harvest areca processing patterns, the yield of areca nuts is less than optimal. The purpose of this study are a). Describe the pattern of post-harvest handling of areca nut in Tanjung Jabung Barat Regency; b). Analyzing the determinants that influence farmers' decisions in choosing post-harvest areca nut management patterns in Tanjung Jabung Barat Regency. The sample of this study was farmers who worked on areca nut in Betara District which consisted of 3 villages namely Tanjung Senjulang Village, Jati Mas Village and Bram Itam Raya Village as many as 78 people from a population of 347 areca nut farmers. The method of determining the sample by simple random sampling. The data analysis method uses multinomial logistic regression analysis. In this study, researchers examined the influence of capital, experience, price, labor, education and technology on pentane decisions to choose between 3 post-harvest areca nut handling patterns. Based on the analysis results it is known that capital, experience and price have a significant effect (p <0.1) on the decision of farmers in choosing pattern 1 in post-harvest handlers. As for labor, education and technology had no significant effect (p> 0.1). Based on the analysis that capital has a significant effect (p <0.1) on the decision of farmers in choosing pattern 2 in post-harvest handling, but for experience, price, labor, education and technology have no significant effect (p> 0.1). Capital, experience and price have a significant effect (p <0.1).